Radioguided occult lesion localization versus wire-guided localization for non-palpable breast lesions: randomized controlled trial - Koray Ocal; Ahmet Dag; Ozgur Turkmenoglu; Emel Ceylan Gunay; Erdem Yucel; Meltem Nass Duce (Clinics, 2011)
AIM: This prospective randomized clinical study was conducted to compare radioguided occult lesion localization (ROLL) with wire-guided localization to evaluate optimum localization techniques for non-palpable breast lesions. METHODS: A total of 108 patients who were undergoing an excisional biopsy for non-palpable breast lesions requiring pathologic diagnosis were randomly assigned to the ROLL group (n = 56) and wire-guided localization group (n = 52). In the study, patients' characteristics, radiological abnormalities, radiological technique of localization, localization time, operation time, weight of the excised specimen, clearance margins, pathological diagnosis and perioperative complications were assessed. RESULTS: There were no differences between the two groups in terms of age, radiological abnormalities and localization technique (p = non-significant for all). ROLL techniques resulted in 100% retrieval of the lesions; for the wire-guided localization technique, 98%. Both localization time and operation time were significantly reduced with the ROLL technique (p = significant for all). The weight of the specimen was significantly lower in the ROLL group than in the wire-guided localization group (p = significant). The overall complication rate and pathological diagnosis were similar for both groups (p = non-significant for all). Clear margins were achieved in 91% of ROLL patients and in 53% of wire-guided localization patients, and the difference was significant. CONCLUSIONS: The present study indicated that the ROLL technique is as effective as wire-guided localization for the excision of non-palpable breast lesions. In addition, ROLL improved the outcomes by reducing localization and operation time, preventing healthy tissue excision and achieving clearer margins.